CASE REPORT: MULTI-MATERIAL ABDOMINAL WALL RECONSTRUCTION SURGERY AFTER MASSIVE DESMOID TUMOR RESECTION - Quang Nhật, Phạm; Thanh Phong, Nguyễn (Journal of Health and Aging, 2025)
Abdominal wall aggressive fibromatosis (Desmoid tumor) is a rare, locally invasive tumor with a high recurrence rate. This study reports a case of surgical resection of a large tumor and multi-material abdominal wall reconstruction, evaluating functional and aesthetic outcomes. A 29-year-old male presented with a 10x15cm abdominal wall mass, diagnosed as Desmoid tumor via biopsy. The patient underwent complete tumor resection, resulting in a significant abdominal defect. Reconstruction was performed using a combination of intraperitoneal onlay mesh (IPOM), rectus abdominis muscle flap, and fascia flap. Pathology confirmed R0 resection. The patient was discharged on day 7 without major complications. At 1-year follow-up, results showed excellent aesthetic and functional recovery with no recurrence. Surgical resection of Desmoid tumors combined with multi-material abdominal wall reconstruction is a feasible approach, ensuring long-term functional and aesthetic success. This case highlights the importance of selecting appropriate reconstruction techniques for large post-resection defects.
Keywords: Desmoid tumor; abdominal wall reconstruction; synthetic mesh; autologous tissue flap; multimodal surgery